Which Occupations Do Unemployed Workers Target? Insights from Online Job Search Profiles - Steffen Altmann; Robert Mahlstedt; Malte Jacob Rattenborg; Alexander Sebald (Institute of Labor Economics (IZA), 2023)
Our study investigates the occupational job search strategies of more than 60,000 unemployed workers in Denmark. We find substantial heterogeneity in how job seekers allocate their search activities across dierent occupations, and this heterogeneity persists throughout the duration of their unemployment spell. Notably, a considerable proportion of unemployed workers (approximately 30%) search in occupations where they lack relevant experiences. Those aiming for jobs unrelated to their prior experience tend to exhibit the lowest levels of employment and earnings, despite the fact that they target occupations with generally favorable conditions.
Keywords: J24; J62; J64; D83; 330; job search; unemployment; occupational mobility; job finding